Illicit affairs: examining the association between types of infidelity and IPV in men and women - Moore, Mariah Dee (Kansas State University, 2024)
Intimate partner violence (IPV) and infidelity are common issues that negatively impact many individuals’ health and relationships. There remains a lack of research examining the association between types of IPV perpetration and victimization and infidelity perpetration and victimization for men and women. Therefore, the current study seeks to answer the following question: Is there a relationship between different types of IPV perpetration and victimization (physical, sexual, psychological, and severe), including minimization and blaming victimization, and infidelity perpetration and victimization for men and women? Our results yielded significant results; namely, women indicated they were more likely to perpetrate severe IPV when infidelity victimization was present, while this finding was not significant for men. In addition, men indicated they were more likely to experience psychological IPV victimization, minimizing victimization, and blaming victimization, as well as perpetrate psychological IPV when infidelity perpetration was present. Our results provide insights into various associations between types of IPV and infidelity perpetration and victimization in intimate partnerships, highlighting the importance of clinicians assessing for infidelity and IPV in relationships and providing helpful tools such as mindfulness and timeouts to prevent further IPV victimization.
Keywords: Intimate partner violence; Infidelity; Gender